The natural forest gaps maintenance diversity of understory birds in Mae Sa-Kog Ma Biosphere Reserve, northern Thailand - SUPALAK SIRI; YUWADEE PONPITUK; MONGKOL SAFOOWONG; DOKRAK MAROD; PRATEEP DUENGKAE (Society for Indonesian Biodiversity, 2019)
Siri S, Ponpituk Y, Safoowong M, Marod D, Duengkae P. 2019. The natural forest gaps maintenance diversity of understory birds in Mae Sa-Kog Ma Biosphere Reserve, northern Thailand. Biodiversitas 20: 181-189. We compared the species composition and feeding guilds between under closed canopies and forest gaps in the low-elevation montane evergreen forest in Mae Sa-Kog Ma Biosphere Reserve. Monthly mist netting was used to capture birds from January 2015 to December 2017. In total, 958 individual birds belonging to 65 species were captured over 25,920 sampling hours. Of the total number of birds, 475 were from 51 species (Shannon-Wiener index: H' 2.974) under closed canopies and 483 were from 47 species (H' 2.985) in forest gaps. The number of bird species in gaps increased rapidly and constantly through 1 year following gap creation. Forest gap localities contained 48% of the understory birds in the area. Foliage–gleaning insectivores were the dominant bird feeding guild in both areas. Some species such as Erythrura prasina is a nomadic bird were found on first year of the forest gap only. Overall, we found that the forest gaps created by natural disturbances in the Mae Sa-Kog Ma Biosphere Reserve had no negative impact on the diversity of understory bird communities. The natural forest gap are created by intermediate disturbance promotes a relatively high biodiversity of birds in the ecosystem.